2018
DOI: 10.1021/acs.bioconjchem.8b00136
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Umbrellas Modulate the Selective Toxicity of Polyene Macrolide Antifungals

Abstract: Antifungal polyene macrolide antibiotics Amphotericin B (AmB) and Nystatin (NYS) were conjugated through the ω-amino acid linkers with diwalled "molecular umbrellas" composed of spermidine-linked deoxycholic or cholic acids. The presence of "umbrella" substituents modulated biological properties of the antibiotics, especially their selective toxicity. Some of the AmB-umbrella conjugates demonstrated antifungal in vitro activity comparable to that of the mother antibiotic but diminished mammalian toxicity, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The AmB conjugates showed comparable antifungal activity and reduced hemolytic activity relative to the parent drug. In contrast, in the case of NY, its conjugates showed reduced antifungal activity and increased toxicity . Meanwhile, the use of a molecular umbrella composed of O-sulfate residues of cholic acid in the synthesis of conjugates with cispentacin (CisP) containing the “trimethyl lock” (TML) or O-dithiobenzylcarbamoyl group resulted in obtaining antifungal compounds without hemolytic properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AmB conjugates showed comparable antifungal activity and reduced hemolytic activity relative to the parent drug. In contrast, in the case of NY, its conjugates showed reduced antifungal activity and increased toxicity . Meanwhile, the use of a molecular umbrella composed of O-sulfate residues of cholic acid in the synthesis of conjugates with cispentacin (CisP) containing the “trimethyl lock” (TML) or O-dithiobenzylcarbamoyl group resulted in obtaining antifungal compounds without hemolytic properties.…”
Section: Resultsmentioning
confidence: 99%
“… Skwarecki et al showed that conjugates containing a dihedral molecular umbrella can penetrate the cell wall in Candida cells. This allows further research to construct more active conjugates with molecules other than cispentacin. , …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, this linker has not been employed so far for the construction of antimicrobial umbrella conjugates. The esterase-triggered TML (‘trimethyl lock’) [ 15 ], applied originally in antibacterial siderophore conjugates [ 16 , 17 ], has been for the first time used for the construction of potential antifungal conjugates.…”
Section: Resultsmentioning
confidence: 99%
“…The most well-known polyene, amphotericin B (AmB), is one of the most potent fungicidal agents on the market with a broad-spectrum of activity, shown to be effective against Cryptococcus spp. and most Candida spp., but several next generation drugs have been in the making [ 3 , 4 , 5 ]. (ii) Azoles are a class of antifungal drugs that target lanosterol-14α-demethylase (Erg11), which catalyzes the demethylation of lanosterol to make an important precursor that is eventually converted into ergosterol [ 6 , 7 ].…”
Section: Fungal Infections In Humans and Current Antifungal Drugsmentioning
confidence: 99%